Online Peer-to-Peer Mentoring Support for Youth with Hemophilia: Qualitative Needs Assessment - Breakey, Vicky R (JMIR Pediatr Parent, 2018)
BACKGROUND: To support adolescents through transition from pediatrics to adult care, health care providers and families help teens gain knowledge and develop self-management skills. Peer mentoring can provide meaningful support and has been associated with improved health outcomes in patients with other chronic conditions. Peer mentoring is an appealing way to provide support, but it is imperative to consider the unique needs of adolescents to ensure its success. OBJECTIVE: The objective of our study was to identify the peer mentoring wants and needs of youth with hemophilia in order to guide the development of a new program. METHODS: In this qualitative study, we interviewed a convenience sample of youth with hemophilia from 2 Canadian hemophilia treatment centers. Two iterative cycles of audiorecorded, semistructured individual interviews were conducted. Descriptive statistics and content analyses were used to organize data into categories that reflected emerging themes. RESULTS: In total, we recruited 23 participants aged 12-20 years, with a mean age of 14.91 (2.57) years. When asked about program design, participants weighed the importance of flexibility in delivery (eg, Web-based, in person, text messaging [short message service]), content (eg, structured vs unstructured), frequency of sessions, and length of the program. Participants identified some potential challenges such as scheduling issues, comfort level for disease discussion, and discordant mentor-mentee personality types. The program was viewed as a positive medium for connecting peers with hemophilia. CONCLUSIONS: Adolescents with hemophilia expressed interest in a peer mentoring program and provided valuable insight that will be applied in the development of a peer mentoring program for youth with hemophilia.